Tsunamis versus extreme meteorological waves: Evidence from the 2004 Aegean Sea cyclone in Samos Island - Stiros, Stathis (Bulletin of the Geological Society of Greece, 2024)
In January 2004 a Mediterranean cyclone in the Aegean Sea seriously affected the north coast of Samos Island, damaged the harbour mole of a coastal village, and catapulted its building material along with heavy boulders to the inner harbour basin. This area was also affected by a 2020, magnitude 7.0 earthquake which produced localized tsunamis. The evidence from the 2004 cyclone, with boulders shifted from known positions and with known trajectories, can contribute to the debate for the causes of mobilization of coastal boulders because of storms, tsunamis, or their combination.